2007
DOI: 10.1210/en.2006-0998
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate Induced Mitochondrial Deoxyribonucleic Acid Damage and Apoptosis in L6 Rat Skeletal Muscle Cells

Abstract: A major characteristic of type 2 diabetes mellitus (T2DM) is insulin resistance in skeletal muscle. A growing body of evidence indicates that oxidative stress that results from increased production of reactive oxygen species and/or reactive nitrogen species leads to insulin resistance, tissue damage, and other complications observed in T2DM. It has been suggested that muscular free fatty acid accumulation might be responsible for the mitochondrial dysfunction and insulin resistance seen in T2DM, although the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
100
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(114 citation statements)
references
References 55 publications
12
100
1
1
Order By: Relevance
“…Independent effects of fatty acids on muscle redox state are, however, also supported by in vitro studies [9,10]. Moreover, the current conditions have direct pathophysiological implications in the postprandial state, when hyperinsulinaemia is associated with variable changes in plasma NEFA concentration depending on meal composition [7,25].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Independent effects of fatty acids on muscle redox state are, however, also supported by in vitro studies [9,10]. Moreover, the current conditions have direct pathophysiological implications in the postprandial state, when hyperinsulinaemia is associated with variable changes in plasma NEFA concentration depending on meal composition [7,25].…”
Section: Discussionmentioning
confidence: 90%
“…Available data also indicate that oxidativestress-induced insulin resistance involves nuclear factor-κB (NFκB) nuclear translocation after nuclear factor-κB inhibitor α (IκBα) phosphorylation and degradation [8]. The potential involvement of chronic NEFA elevation in highfat-diet-induced changes in muscle oxidative stress, inflammation and insulin action is suggested by in vitro studies [9,10], and fatty acids are also reported to induce insulin resistance in vivo [11,12]. In addition, the onset of oxidative stress and inflammation during chronic high-fat or highenergy feeding has been reported to lower skeletal muscle mitochondrial oxidative capacity [13,14], and this alteration could contribute to insulin resistance through impaired muscle lipid oxidation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, the data indicate that glucose acts through the PI 3-kinase/Akt/tuberin pathway to downregulate OGG1, resulting in the accumulation of oxidized DNA. 8-OxodG is a product of oxidative DNA damage following specific enzymatic cleavage after the ROS-induced 8-hydroxylation of guanine bases in the mitochondrial and nuclear DNA (11,12). 8-OxodG is known to be a sensitive marker of oxidative DNA damage and of the total systemic oxidative stress in vivo (13).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which they elicit these protective effects are unclear, although reductions in the magnitude of steatosis, oxidative stress and inflammatory pathway activation appear to be involved. Since long chain saturated fatty acids promote oxidative stress and activate inflammatory pathways in cells and tissues not exposed to alcohol [29,37,46,[98][99][100], it seems likely that the presence of alcohol alters metabolism of specific fatty acids within tissues. Subsequent studies that directly compare the effect of saturated fatty acids in models of alcoholic-and nonalcoholic fatty liver disease are needed to address these discrepancies.…”
Section: A Dilemma: Saturated Fatty Acids Are Protective In Alcohol-imentioning
confidence: 99%